2019
DOI: 10.1159/000500299
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical Resident Exposure to Pediatric Neurosurgery: An Analysis of Resident Case Logs

Abstract: <b><i>Introduction:</i></b> The purpose of this study is to identify the national trends of exposure to pediatric procedures during neurosurgical residency and to subsequently evaluate how neurosurgery residents’ experiences correlate with the minimum requirements set forth by the American College of Graduate Medical Education (ACGME). <b><i>Methods:</i></b> ACGME resident case logs from residents graduating between 2013 and 2017 were retrospectively reviewed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…[1,2,9,12] White et al found that the average number of pediatric neurosurgical cases performed per resident between the years 2013 and 2017 was 98.8, which was less than the average numbers for operations on adult patients. [13] At our practice, the lockdown did not seem to significantly impact the number of cases for the rotating resident and is unlikely to affect the ACGME requirements of pediatric cases for graduation. e pediatric rotation here is a bridge from junior residency to senior residency and is often when our residents learn to hone their microsurgical skills operating under a microscope.…”
Section: Pediatricsmentioning
confidence: 64%
“…[1,2,9,12] White et al found that the average number of pediatric neurosurgical cases performed per resident between the years 2013 and 2017 was 98.8, which was less than the average numbers for operations on adult patients. [13] At our practice, the lockdown did not seem to significantly impact the number of cases for the rotating resident and is unlikely to affect the ACGME requirements of pediatric cases for graduation. e pediatric rotation here is a bridge from junior residency to senior residency and is often when our residents learn to hone their microsurgical skills operating under a microscope.…”
Section: Pediatricsmentioning
confidence: 64%
“…The current study demonstrates that although residents on average log more than three times the required number of pediatric cases, 8 pediatric neurosurgery exposure during residency training remains extremely variable. Much of this is probably due to the institution-dependent exposure to pediatric neurosurgery and the lack of a stan- Our study was limited by the subjective nature of a survey and an incomplete cohort (77.4% response rate).…”
Section: Discussionmentioning
confidence: 88%
“…Of note, the study also demonstrated a significant decrease in the number of cases logged during this interval. 8 Case volumes alone may not provide enough information, given the significant variability in case volume measurements that have been reported across multiple fields, especially in increasingly subspecialized fields. In a sur- 9 Exposure to pediatric surgery is also quite varied among programs.…”
Section: Discussionmentioning
confidence: 99%